2017
DOI: 10.1044/2017_aja-17-0008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Depression in Patients With Tinnitus and Hyperacusis

Abstract: Those involved in the management of patients with tinnitus and/or hyperacusis should use a wide range of instruments to assess the full impact of tinnitus on a patient's life and should be prepared to refer a patient for treatment for depression, especially when the patient has anxiety, hyperacusis, and/or insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 44 publications
2
36
0
1
Order By: Relevance
“…Mechanisms underlying hyperacusis following mTBI are unknown, although proposed theories suggest a tonotopic reorganization and hyperexcitability of the auditory cortex involving a malfunction of 5-HT (61), a release of endogenous opioid peptides (62), and a decreased GABA A -mediated inhibition in the inferior colliculus (63). Many studies have shown that the sleep disturbance generated by hyperacusis is mediated by psychological factors (58,64,65). Anxiety and hyperresponsiveness to every sound while one is trying to sleep could result in insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms underlying hyperacusis following mTBI are unknown, although proposed theories suggest a tonotopic reorganization and hyperexcitability of the auditory cortex involving a malfunction of 5-HT (61), a release of endogenous opioid peptides (62), and a decreased GABA A -mediated inhibition in the inferior colliculus (63). Many studies have shown that the sleep disturbance generated by hyperacusis is mediated by psychological factors (58,64,65). Anxiety and hyperresponsiveness to every sound while one is trying to sleep could result in insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms underlying hyperacusis following mTBI are unknown, although proposed theories suggest a tonotopic reorganization and hyperexcitability of the auditory cortex involving a malfunction of 5-HT [61], a release of endogenous opioid peptides [62], and a decreased GABA Amediated inhibition in the inferior colliculus [63]. Many studies have shown that the sleep disturbance generated by hyperacusis is mediated by psychological factors [58,64,65]. Anxiety and hyperresponsiveness to every sound while one is trying to sleep could result in insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the severity of tinnitus and sleep disturbances has been highlighted by several authors (Tyler and Baker, 1983;Meikle et al, 1984;Folmer and Griest, 2000;Schecklmann et al, 2015;Cronlein et al, 2016). Recent studies suggest that more than 70% of patients seeking help for tinnitus from a specialized audiology clinic within the UK National Health Service (NHS) also had insomnia (Aazh et al, 2016;Aazh and Moore, 2017a;Aazh et al, 2017;. It has been reported that the emotional and cognitive distress caused by tinnitus has a significant relationship with the severity of sleep disturbances (Cronlein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%